1981
DOI: 10.1172/jci110039
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in bone mineral density of the appendicular and axial skeleton with aging: relationship to spinal osteoporosis.

Abstract: A B S T R A C T Patterns ofbone loss in the axial and the appendicular skeleton were studied in 187 normal volunteers (105 women and 82 men; age range, 20-89 yr) and in 76 women and 9 men with vertebral fractures due to osteoporosis. Bone mineral density was measured in vivo at the lumbar spine (predominantly trabecular bone) by dual photon absorptiometry and at the midradius (>95% cortical bone) and distal radius (75% cortical and 25% trabecular bone) by single photon absorptiometry. In normal women, bone dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
311
6
17

Year Published

1982
1982
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,132 publications
(361 citation statements)
references
References 19 publications
(16 reference statements)
23
311
6
17
Order By: Relevance
“…The significant correlations found between BMD at both skeletal sites and factors such as age, height, and weight in RA patients have been previously observed in studies of normal subjects (24) and were seen in our own control groups. The significant differences in age between patients and controls of both sexes (Table 1) were corrected for by comparing regressions of BMD against age.…”
Section: Discussionsupporting
confidence: 84%
“…The significant correlations found between BMD at both skeletal sites and factors such as age, height, and weight in RA patients have been previously observed in studies of normal subjects (24) and were seen in our own control groups. The significant differences in age between patients and controls of both sexes (Table 1) were corrected for by comparing regressions of BMD against age.…”
Section: Discussionsupporting
confidence: 84%
“…From the data presented here and elsewhere, 6,15,16,18,20,22,23,29 the natural history of bone mass loss appears to be di erent depending on whether it is due to immobilization, menopause, hormonal, or age related factors. The di erences between our results and the studies available in the literature may be explained by the special population included in our study.…”
Section: Discussionmentioning
confidence: 67%
“…These results are contrary to Chantrine A et al 15 and Uebelhart et al 25 Possible reasons for the higher than normal BMD in the lumbar spine in our population might be that (1) the lumbar spine has become the primary weight bearing region or (2) neuropathic osteoarthropathy consisting of disk space loss, bone sclerosis, fragmentation, osteophytosis, and subluxation as well as degenerative disease which may have caused di used increased radiodensity of the spinal column. 26 ± 28 Riggs et al 22 showed that in normal men vertebral and appendicular bone diminution with aging was minimal or insigni®cant. In cross-sectional and longitudinal studies, Biering-Sorensen et al 15,16 showed that BMC of the femoral bone was continuously and signi®cantly decreased (25% lower) in spinal cord injured patients between the age of 20 and 55 compared to normal individuals, while the BMC of the lumbar spine was nearly unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The surface area of cancellous trabecular bones such as the epiphysis of long bones as well as the lumbar vertebral body is larger than that of compact bone, such that the bone transition of the cancellous bone is greater than that of the compact bone when estrogen is not sufficient . Riggs (Riggs et al, 1981) reported that the reformation rate of cancellous bone was nine times higher than that of compact bone. Cortical osteoporosis begins in the late stage of osteoporosis.…”
Section: Prevention Of Osteoporosis In Micementioning
confidence: 99%